Impact of Temperature on the Reproductive Development in Mungbean (Vigna radiata) Varieties under Different Dates of Sowing - Tzudir, L.; Bera, P. S.; Chakraborty, P. K. (International Journal of Bio-resource and Stress Management, 2023)
A two year (2010 and 2011) experiment was conducted on four mungbean varieties (V1-Pant Mung-5, V2-Bireswar, V3-RMG-62 and V4-Sukumar) sown on three different dates (D1-15th February, D2-1st March, D3-15th March) in a split plot design (Main plot-dates of sowing and Sub plot-variety) in the Student’s Instructional Farm, BCKV, West Bengal. The reproductive components such as bud, flower and pod numbers plant-1 and pod:flower ratio were recorded from 25 to 46 days after emergence (DAE). The relationship between the mean air temperature and different reproductive components were computed. Bud number per plant was maximum on 34 DAE when sown on D2, while it was maximum on 37 DAE under D1 and D3 sown crops. Highest number of flower per plant was observed on 37 DAE irrespective of dates of sowing, whereas, the maximum number of pods per plant was observed on 46 DAE. Among the dates of sowing, the D2 sown crop recorded significantly higher number of bud, flower and pod. Among the four varieties, Pant Mung-5 recorded the maximum number of bud, flower and pod per plant. Pod: flower ratio under 1st March sowing was highest under 37 to 40 DAE. With the advancement of age, the D3 sown crop recorded highest pod:flower ratio. Number of buds per plant was found to be significantly related to the mean air temperature in 2010 under different varieties, but in 2011, it was insignificant. However, the number of flower and pod per plant were significantly related to the mean air temperature in both the year. Increased temperature increased the number of flower plant-1 but the reverse was true in case of pod. Increased temperature under delayed sowing significantly reduced the pod number plant-1. A temperature range of 27 to 32°C was found to be congenial for the reproductive development in mungbean.